A Comprehensive Evaluation of a Novel Color Range Indicator in Multiple Blood Glucose Meters Demonstrates Improved Glucose Range Interpretation and Awareness in Subjects With Type 1 and Type 2 Diabetes. (November 2016) - Grady, Mike; Katz, Laurence B.; Cameron, Hilary; Levy, Brian L.
Aims: We previously demonstrated that people with type 2 diabetes (T2DM) can improve their ability to categorize blood glucose (BG) results into low, in range, or high glycemic ranges after experiencing a color range indicator (CRI or ColorSure™ Technology) in a single meter. This study examined whether a CRI was effective in people with type 1 (T1) or T2DM when used in 3 glucose meters. Methods: A total of 179 subjects (139 T2DM and 40 T1DM) classified BG values as low, in range, or high based on individual current knowledge. Subjects then experienced the CRI which showed whether different BG values were low, in range, or high. After CRI interaction, subjects repeated the classification. Results: Following interaction with the CRI, subjects significantly improved their ability to categorize BG results into low, in range, and high glycemic ranges by 27.9% (T2DM) and 27.2% (T1DM) (each P < .001). Improvement was not accompanied by an increase in time spent categorizing results. There was no difference in classification ability between subjects with T1 or T2DM. There was also no correlation between HbA1c, numeracy level, test frequency, or duration of diabetes and the ability to correctly classify results. Subjects agreed the CRI feature helped them easily interpret glucose values and improved their awareness of glucose ranges. Conclusion: Interaction with a CRI improved the ability of subjects with T1 and T2DM to interpret and categorize BG values into recommended glycemic ranges, irrespective of the glucose meter providing the CRI insights.